PSYCHOLOGICAL WELL-BEING SEBAGAI FAKTOR PENDUKUNG REHABILITASI TAHANAN NARKOTIKA DI LAPAS BADAN NARKOTIKA NASIONAL (BNN) SUMATERA SELATAN - Sindy Aulya Maharani; Shal Sabil Lamanda; Henny Yusalia (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Drug abuse not only impacts physical health but also affects an individual's psychological health. Therefore, successful rehabilitation is determined not only by recovery from substance dependence but also by the psychological well-being of the rehabilitation participants. This study aims to describe the role of psychological well-being as a supporting factor in the rehabilitation of drug inmates at the National Narcotics Agency (BNN) South Sumatra Prison. The research method used was a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation during the rehabilitation program. The results indicate that psychological well-being plays a role in increasing motivation to recover, helping inmates accept themselves, build more positive social relationships, and foster hope and purpose in life after undergoing rehabilitation. Various development programs, such as counseling, religious activities, and skills training, also support the improvement of psychological well-being of rehabilitation participants. Good psychological well-being helps individuals cope with stress during the recovery process and strengthens their readiness to return to optimal functioning in society. These findings indicate that psychological well-being is an important aspect that needs to be considered in the implementation of drug rehabilitation because it can support successful recovery and reduce the risk of relapse.